Analisis Dampak Kekosongan Hukum Pembaruan Perjanjian Kerja Waktu Tertentu Terhadap Perlindungan Hukum Pekerja: Penelitian - Engel Thomas Rumfaan; Joko Widarto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The amendment to the regulation of the Fixed-Time Work Agreement (PKWT) through Law Number 6 of 2023 as an amendment to Law Number 13 of 2003 has eliminated the provisions regarding the PKWT renewal mechanism that was previously strictly regulated. The term and extension of PKWT were then transferred to government regulation number 35 of 2021 without being followed by an explicit renewal arrangement. This condition raises legal issues related to legal certainty and legal protection of workers in PKWT employment relationships. The urgency of this research lies in the void of PKWT renewal arrangements that have the potential to weaken legal protection for workers. This study aims to analyze the regulation of the PKWT period after changes in laws and regulations and the impact of the vacancy in the regulation of PKWT renewal on the legal protection of workers. The research method used is normative legal research with a legislative approach and a conceptual approach, using primary and secondary legal materials. The results of the study show that the vacancy in the regulation of PKWT renewal creates norms that have the potential to weaken preventive legal protection for workers, especially related to the certainty of employment relationship status and the prevention of repeated use of PKWT. From the perspective of legal certainty and legal protection theory, these changes have not been able to fully guarantee a balance of employment relations between employers and workers.